(untitled) (Biological Sciences - PJSIR, 2000)
The genetic yield potential of today’s cotton plant is at least five and probably close to ten times the average yields we obtain each year. The primary cause of potential yield reduction is the unfavourable physical environment, includ- ing radiation, temperature and water supply. Water stress from excess water is a greater problem to stand establishment and seedling survival than is limited water supplies. However, the emphasis is nowadays on short season cotton production with the release of new higher yielding and early maturing varieties. Therefore there is need for more information about initial irrigation and frequency of irrigation.